United European Gastroenterology (UEG) and European Society for Neurogastroenterology and Motility (ESNM) consensus on gastroparesis. Issue 3 (3rd May 2021) - Schol, Jolien; Wauters, Lucas; Dickman, Ram; Drug, Vasile; Mulak, Agata; Serra, Jordi; Enck, Paul; Tack, Jan; ,
Abstract: Background: Gastroparesis is a condition characterized by epigastric symptoms and delayed gastric emptying (GE) rate in the absence of any mechanical obstruction. The condition is challenging in clinical practice by the lack of guidance concerning diagnosis and management of gastroparesis. Methods: A Delphi consensus was undertaken by 40 experts from 19 European countries who conducted a literature summary and voting process on 89 statements. Quality of evidence was evaluated using grading of recommendations assessment, development, and evaluation criteria. Consensus (defined as ≥80% agreement) was reached for 25 statements. Results: The European consensus defined gastroparesis as the presence of symptoms associated with delayed GE in the absence of mechanical obstruction. Nausea and vomiting were identified as cardinal symptoms, with often coexisting postprandial distress syndrome symptoms of dyspepsia. The true epidemiology of gastroparesis is not known in detail, but diabetes, gastric surgery, certain neurological and connective tissue diseases, and the use of certain drugs recognized as risk factors. While the panel agreed that severely impaired gastric motor function is present in these patients, there was no consensus on underlying pathophysiology. The panel agreed that an upper endoscopy and a GE test are required for diagnosis. Only dietary therapy, dopamine‐2 antagonists and 5‐HT4 receptor agonists were considered appropriate therapies, in addition to nutritional support in case of severe weight loss. No consensus was reached on the use of proton pump inhibitors, other classes of antiemetics or prokinetics, neuromodulators, complimentary, psychological, or more invasive therapies. Finally, there was consensus that gastroparesis adversely impacts on quality of life and healthcare costs and that the long‐term prognosis of gastroparesis depends on the cause. Conclusions and Inferences: A multinational group of European experts summarized the current state of consensus on definition, symptom characteristics, pathophysiology, diagnosis, and management of gastroparesis. Key Summary: Current knowledge The epidemiology of gastroparesis is not well known. Diagnosis and treatment of gastroparesis is challenging due to uncertainties in definition and optimal therapeutic approach. What is new here A Delphi panel consisting of 40 experts from 19 European countries established the level of consensus on 89 statements regarding gastroparesis. The statements reaching consensus serve to guide clinicians in recognizing, diagnosing and treating gastroparesis in clinical practice. The statements without consensus identify areas in need of future research.